Optimal sizing and placement of D-SVC in radial distribution systems using an exhaustive analytical search - Malčeski, Stojan; Vuletić, Jovica; Todorovski, Mirko; Angelov, Jordančo (SAGE Publications, 2022)
Throughout the past few decades, the share of distributed generation in power systems has increased continuously. This increasing trend coupled with the continuous demand growth in the distribution systems started a shift towards heavier reactive power consumption. The latter paved the way for the development of advanced operational and planning algorithms for power distribution systems. Following these trends in the distribution systems, the distribution grids must be developed with greater reliability and flexibility, i.e. smart grids. Consequently, the implementation of smart technologies instead of traditional ones should be considered wherever feasible. This paper presents an approach for optimal placement, economic sizing, and operation point search of distribution static VAR compensator (D-SVC) using an exhaustive analytical search. The proposed algorithm introduces quite a few novelties, unique, superior, and repetitive results presented on a distribution test system IEEE 69.